Facile synthesis of novel nanocurcuminoids–sacha inchi oil using the phase inversion temperature method: Characterization and antioxidant activity - Trần, Quang Hiếu (Wiley, 2022)
A nanocurcuminoids emulsion (NCE) was successfully synthesized via the phase inversion temperature (PIT) method combining magnetic stirring. Factors affecting the fabrication of this material, including emulsifier concentration, types of oils, tem perature, and stirring time, were investigated. Results showed that the synthesized efficiency obtained 94.56 ± 3.78% at 11% of emulsifier concentration, 2% of sacha inchi oil with 5,000 rpm of shaking speed within 25 min of reaction time at 80°C. Besides, dynamic light scattering analysis presents that NCE gets 24.1 ± 2.9 nm of the average diameter, −10.4 ± 0.8 mV of zeta potential (ZP), and 0.173 ± 0.021 a.u of the polydispersity index (PDI) at the optimal condition. Moreover, the prepared NCE was stable at the ionic strength of NaCl 0.5 M and pH of 7 after 60 days of storage. In particular, the antioxidant activity of this NCE was slightly higher than that of free curcuminoids